PECULIARITY OF CULTIVATION OF COULIFLOWER AND BROCCOLI IN EDAPHIC-CLIMATIC ZONE OF PLAIN, PIEDMONT, AND MOUNTAIN PROVINCES OF DAGESTAN - Ye. G. Gadjimustapaeva; G. G. Rabadanov (Овощи России)
Results of the study of possibility of cultivation of cauliflower and broccoli in the context of vertical zonality of Dagestan are presented. Physiological  characteristics, agriculture, and cultivation of early maturing varieties of cauliflower and broccoli during spring, summer, and autumn in condition of plain, piedmont, and mountain regions of Dagestan were studied. The high quality product of these crops was obtained in condition of Dagestan in the altitude of 1510 m above sea level.